2016
DOI: 10.1302/0301-620x.98b3.35508
|View full text |Cite
|
Sign up to set email alerts
|

Total elbow arthroplasty for non-rheumatoid patients with a fracture of the distal humerus

Abstract: The surgeons undertaking these procedures should be aware of the long-term revision rates and also the gender difference in the rates of loosening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…The long-term survival rate of elbow arthroplasty is still lower than that for hip or knee arthroplasty,[ 12 ] and almost half of the patients need revision surgery within 10 years. [ 13 ] Bone defects are a critical problem in arthroplasty because both humerus and ulna are smaller than the femur and tibia. Furthermore, less bone storage exists in the ulna, thus making it more difficult to stabilize the prosthesis during revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term survival rate of elbow arthroplasty is still lower than that for hip or knee arthroplasty,[ 12 ] and almost half of the patients need revision surgery within 10 years. [ 13 ] Bone defects are a critical problem in arthroplasty because both humerus and ulna are smaller than the femur and tibia. Furthermore, less bone storage exists in the ulna, thus making it more difficult to stabilize the prosthesis during revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of total elbow arthroplasty for acute distal humeral fractures with mean follow-up of at least 2 years are summarized in Table 1. 19,21,42,60,[67][68][69][70][71][72][73][74][75][76][77] Surgical interventions for intra-articular fractures aim to restore painless, functional range of motion. A functional flexion-extension arc of motion for the elbow has traditionally been defined as 100° (range, 30°-130°), and the average arcs reported in the studies the authors reviewed ranged from 85° to 122.5°.…”
Section: Total Elbow Arthroplastymentioning
confidence: 99%
“…In their systematic review, Voloshin et al 25 reported a 21.5%±9.2% overall complication rate with total elbow arthroplasty for acute distal humeral fractures, consistent with findings of the studies the current authors reviewed. 19,21,42,60,[67][68][69][70][71][72][73][74][75][76] Common complications include ulnar nerve dysfunction, triceps weakness or rupture, wound issues, infection, and aseptic loosening or mechanical complications.…”
Section: Total Elbow Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…Prasad et al . [ 42 ] analysed the survival of TEA in fracture patients and showed that only 53% had implant survival of more than 10 years and 89.5% of patients demonstrated loosening of their prostheses at this stage.…”
Section: Elbow Arthroplastymentioning
confidence: 99%